Human milk: composition and health benefits - Fabio Mosca; Maria Lorella Giannì (PAGEPress Publications, 2017)
Breastfeeding is widely acknowledged as the normal and unequalled method for feeding infants due to its associated health benefits, both for the infant and the mother. The World Health Organization recommends that infants are exclusively breastfed up to the completion of six months of age, with  breastfeeding continuing to be an important part of the diet until the infant is at least two years old. The several health benefits associated with breastfeeding are driven by the combined action of the nutritional and bioactive components in human milk and the magnitude of the majority of the ascertained biological effects is directly dependent on breastfeeding duration. This review briefly summarizes the current knowledge on the composition of human milk and provides an overview on its functional effects on health outcomes, focusing on the latest research results.